Travel with books: Selangor smart bus - Wan Hasnol, Wan Mohd Hafiz; Razali, Rosfatin Suriani; Abdullah, Nor Asfasyuhada; Othman, Nurul Hanan (Universiti Teknologi MARA, Kedah, 2017)
Mobile Bus Library service is a common service provided by public libraries all around the world. The Travel with Books Smart Bus of Selangor is a little bit different than the common mobile bus library because it is provided in each of the Selangor Smart Bus free public transport service. The Selangor Smart Bus service is made available to the whole state of Selangor by the state government. Perbadanan Perpustakaan Awam Selangor (PPAS) is another Selangor state agency which provide library service. Together, these two agencies will combine their effort to encourage reading habit by extending its service outside the library building and into buses frequented daily by passengers all over Selangor state through the Travel with Books project. People who ride the bus will occupy their time with reading as alternative to other activities, especially with the long ride. The “Travel with Book” service is not a common mobile bus library service provided by most public libraries. It is a library in a free public transport service system where books are made available to bus passengers as a mean to encourage reading habit and to avoid boredom when using public transportation system, especially when the ride is also tagged as ‘free” public transport